PREDICTING MALAYSIAN UNIVERSITY STUDENTS' INTENT TO PURSUE RETAILING CAREER: APPLICABILITY OF THEORY OF PLANNED BEHAVIOR - Mokhlis S.; Hussin N.S.N.; Nizam N.Z.; Noor N.A.M.; Muslim N.A. (AOS-Estratagia and Inovacao, 2023)
Purpose:The retail industry offers diverse and unique career paths. However, despite the high demand for new graduates to fill managerial positions in the retail sector, their reluctance to pursue a retail career remain. This study aims to investigate the antecedents that predict retail career intention of Malaysian undergraduate business students. Theoretical framework: Using Ajzen's (1991) Theory of Planned Behavior (TPB) as the underpinning theoretical framework, this study hypothesized that students' intent to pursue a career in retailing are influenced by the three independent variables in TPB (attitude, subjective norm, and perceived behavioral control) and the additional variable of knowledge. Methodology: Data were collected via an online survey among a sample of 316 undergraduate business students from three public universities in Malaysia. Structural equation modelling approach was used to assess the strength of the hypothesized relationships of the proposed model simultaneously via the two-stage model building process. Findings:Results indicate that students' attitude, subjective norm, and knowledge significantly predicted students' intent to pursue a career in retailing, but perceived behavioral control surprisingly did not. All the four explanatory variables in TPB explained about 76 percent of the variance in behavioral intention to pursue a retail career. Research, Practical & Social implications: Findings of this study clearly supports the applicability of the TPB in predicting students' intent to pursue a career in retailing. Results obtained can serve as a basis for future works in this area. This study also offers implications for educators and industry practitioners to foster retail career intentions among students. Originality: This study is a pioneering attempt to test the applicability of the TPB as a theoretical framework to predict university students' retail career intention. The Author(s), 2022.